Contribution of modern social networks in building social integration in public Universities in Uganda - Nareeba, Peter; Ichuloi PhD, Dr. Anthony; Were PhD , Prof. Edmond (International Journal of Scientific Research and Management (IJSRM), 2019)
The study investigated the Contribution of modern social networks in building social integration in five public Universities in Uganda with a target population of 266 students’ groups. It employed multi-stage sampling technique, comprising of purposive and simple random sampling to select 57 students’ groups with a total of 456 respondents. Data collection tools comprised of questionnaires and interview schedules. The findings indicate that the most interrogating issue was that a majority of the respondents revealed that social media has negative effects on social integration. The results revealed that unity among students enables them acquire a sense of belonging as a body of students, hence enhancing social cohesion within the social groups. WhatsApp was ranked at position one with a mean grade of 1.17 with the percentage of 86.1% ranking it at first position. It was closely followed by Facebook with rank two with a mean grade of 1.66 with 38.5% ranking it at second positionThe study therefore recommends universities’ administration to formulate accommodative policies that properly regulate the use of social network platforms. The study also recommended public universities to strengthen organs and institutions that deal with proper management of social networks in their instructions.